Hubungan Suhu Tubuh Dengan Kejadian Mortalitas Pada Pasien Stroke Perdarahan Intraserebral Di Rsud Mardi Waluyo Blitar Tahun 2016 - Sri Haryuni (Akademi Keperawatan Dharma Husada Kediri, 2017)
Stroke is the rapidly developing clinical signs due to focal brain dysfunction (or global), with symptoms lasting for 24 hours or more, can cause death, with no cause other than vascular. This research aims to know the body temperature relationship with the incidence of stroke mortality in patients with intracerebral hemorrhage. Design Retrospective cohort study. The sample 73 samples. This study used simple random sampling method. Stroke PIS determined by clinical and CT scan, mortality was measured by complete medical records. Data were analyzed using Spearman Rank (Rho) with SPSS with significant α = 0.05. The results of the test statistics in get p value 0.000 with α <0.05 there was a relationship between body temperature with the incidence of stroke mortality in patients with intracerebral hemorrhage in hospitals Mardi waluyo Blitar 2016. with a value of temperature coefficient correlation with the incidence of stroke patients with intracerebral hemorrhage mortality of OR = .775. This research There is a significant relationship between body temperature with the incidence of stroke mortality in patients with intracerebral hemorrhage in hospitals Mardi Waluyo Blitar 2016. This study recommends the importance of health workers monitors body temperature patients with stroke intracerebral hemorrhage to reduce death of the patient. Keywords: Body Temperature, Mortality, Stroke Intracerebral Hemorrhage.